RUNAWAY STARS AS THE RESULT OF THE GRAVITATIONAL COLLAPSE OF PROTOSTELLAR CLUSTERS - RUIZ, J; POVEDA, ARCADIO; ALLEN, CHARLES GRANT (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1969)
Some of the difficulties in our present understanding of the origin of run-away stars and expanding clusters are briefly discussed; an alternative explanation for these phenomena is proposed here as the result of dynamical interactions during the collapse
BOL OBS TONAN TACUB
Keywords: RESULT, GRAVITATIONAL COLLAPSE, PROTO, STELLAR CLUSTERS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS